2010
DOI: 10.1073/pnas.0915174107
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and CTLA-4 combination blockade expands infiltrating T cells and reduces regulatory T and myeloid cells within B16 melanoma tumors

Abstract: Vaccination with irradiated B16 melanoma cells expressing either GM-CSF (Gvax) or Flt3-ligand (Fvax) combined with antibody blockade of the negative T-cell costimulatory receptor cytotoxic T-lymphocyte antigen-4 (CTLA-4) promotes rejection of preimplanted tumors. Despite CTLA-4 blockade, T-cell proliferation and cytokine production can be inhibited by the interaction of programmed death-1 (PD-1) with its ligands PD-L1 and PD-L2 or by the interaction of PD-L1 with B7-1. Here, we show that the combination of CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
1,304
5
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,643 publications
(1,389 citation statements)
references
References 27 publications
61
1,304
5
19
Order By: Relevance
“…As the clinical development of anti-PD-1 anti bodies proceeded, a growing body of research suggested an added benefit in tumour response when administered in combination with an anti-CTLA-4 antibody 91 . From a mechanistic perspective, this finding was consistent with the contrasting role of PD-1 in regulating the effector phase of the immune response, as opposed to the role of CTLA-4 in mediating the priming phase.…”
Section: Immunotherapy With Immune-checkpoint Inhibitorsmentioning
confidence: 99%
“…As the clinical development of anti-PD-1 anti bodies proceeded, a growing body of research suggested an added benefit in tumour response when administered in combination with an anti-CTLA-4 antibody 91 . From a mechanistic perspective, this finding was consistent with the contrasting role of PD-1 in regulating the effector phase of the immune response, as opposed to the role of CTLA-4 in mediating the priming phase.…”
Section: Immunotherapy With Immune-checkpoint Inhibitorsmentioning
confidence: 99%
“…Curran et al reported, in mice xenograft, that the combination of CTLA-4 and PD-1 blockade determines the accumulation of CTLA-4/PD-1 double-positive T effector cells within B16 melanoma cell lines [77]. These data suggest that T cells that would otherwise be functionally and proliferatively repressed are instead able to continue expanding and carrying out effector functions.…”
Section: Clinical Trials and Future Developmentsmentioning
confidence: 99%
“…Although the targets of these drugs both do the same job, silencing T cells, they do so in different ways: CTLA 4 prevents the activation of T cells; PD 1 blocks the cells once they have infil trated the tumour and its environment. And treating mice with compounds that block both proteins yielded a more inflamed tumour as well 3 . "There was reason to think that if you block both, the T cells will be even more ready to kill the tumours, " says Michael Postow, an oncologist at Memorial Sloan Kettering.…”
Section: Mixing It Upmentioning
confidence: 99%